Compulsory Use of the Backboard is Associated with Increased Frequency of Thoracolumbar Imaging. (4th July 2018) - Clemency, Brian M.; Tanski, Christopher T.; Gibson Chambers, Jennifer; O'Brien, Michael; Knapp, Andrew S.; Clark, Alexander J.; McGoff, Patrick; Innes, Johanna; Lindstrom, Heather A.; Hostler, David
Abstract: Background : Backboards have been shown to cause pain in uninjured patients. This may alter physical exam findings, leading emergency department (ED) providers to suspect a spinal injury when none exists resulting in additional imaging of the thoracolumbar spine. New York had previously employed a "Spinal Immobilization" protocol that included compulsory backboard application for all patients with suspected spinal injuries. In 2015, New York instituted a new "Spinal Motion Restriction" protocol that made backboard use optional for these patients. The objective of this study was to determine if this protocol change was associated with decreased backboard utilization and ED thoracolumbar spine imaging.Methods : This was a retrospective before-and-after chart review of subjects transported by a single emergency medical services (EMS) agency to one of four EDs for emergency calls dispatched as motor vehicle collisions (MVC). EMS and ED data were included for all calls within a 6-month interval before and after the protocol change. The protocol change was implemented in the second half of 2015. Subject demographics, backboard use, and spine imaging were reviewed for the intervals January–June 2015 and January–June 2016.Results : There were 818 subjects in the before period and 796 subjects in the after period. Subjects were similar in terms of gender, age and type of MVC in both periods. A backboard was utilized for 440 (54%) subjects in the before period and 92 (12%) subjects in the after period (p < 0.001). ED thoracic spine imaging was performed on 285 (35%) subjects in the before period, and 235 (30%) subjects in the after period (p = 0.02). ED lumbar spine imaging was performed for 335 (41%) subjects in the before period, and 281 (35%) subjects in the after period (p = 0.02).Conclusion : A shift from a spinal immobilization protocol to a spinal motion restriction protocol was associated with a decrease in backboard utilization by EMS providers and a decrease in thoracolumbar spine imaging by ED providers.